PENGARUH PEMANFAATAN TEKNOLOGI DAN INFORMASI PENDIDIKAN, MOTIVASI KERJA KEPALA SEKOLAH DAN KINERJA KEPALA SEKOLAH TERHADAP EFEKTIVITAS PENGELOLAAN SMP NEGERI KOTA SAMARINDA - ZAHRA, RITA (Jurnal Ilmiah Educational Management, 2015)
The purpose of this study is to know the effect of information technology using toward the effectiveness of school management, the effect of work motivation of principle toward the effectiveness of school management, management, the effect of joint information technology using, work motivation of principle, the performance of principle toward the effectiveness of school management. The method of this study uses survey method, with a population of affordability of 60 units of State Junior High Schools of Kalimantan Timur. As conclusion of this study that is using information technology, work motivation of principle,and the performance of principle has a positive effect toward the effectiveness of school management, there is a positive effect of joint information technology using, work motivation, the performance of principle on the effectiveness of school management , the effectiviness of school management can be increased through the information technology,work motivation of principle and performance of principle.